Bosanska nacija / The Bosnian Nation: Demokratska nacija-država versus država zatočena u etnopolitiku / Democratic National State Versus State Trapped within Ethno Politics - Lavić, Senadin (Pregled: časopis za društvena pitanja / Periodical for social issues, 2020)
In this paper the question of a Bosnian nation has been raised, the question that has been continuously disputed and falsified. The question of the Bosnian nation’s constitution and establishment in the 20th century is directed into the blind alley and prevented from being similar to one in other European countries and national states because it has consistently remained at the level of ethnicity ideology, ethno-religious definition of social groups and represented Bosnia as the country and state of “the peoples.” It looked like as there were nowhere in Europe multiethnic state anymore! At one time, at the Fin de siècle, the national was conceived as “Bosniak” at the time of B. Kallay (“integral Bosniakhood”), but historically it was already unfeasible and condemned to failure because Serbian and Croat ethnic and national identities in Bosnia had already been seriously grounded and without the need for re-defining. That attempt to establish a common identity on the Bosniak one represented the founding of a nation on ethnic determination and failed. It imitated the Serbian and Croatian way of understanding the national question as an ethnic one. The other possibility that could after the WW2 follow the Declaration on the Rights of Citizens of Bosnia and Herzegovina from the 2nd ZAVNOBiH Session was not used and Bosnia remained a state of both Bosniaks and Serbs and Croats. The only missing thing was a small step in the direction of statement- Bosnia is Bosnian, it is the state of Bosnians, all its citizens. This would open the door to establishing a Bosnian state identity. When it comes to the history of Bosnia, it is evident that it has not yet been attempts to build a Bosnian national identity on the totality of people living in Bosnia, its citizens, irrespective of their ethnic, religious, linguistic or any other identity constituent element. This means that until now there has not been an adequate Bosnian political philosophy of liberalism and democracy. The capabilities of state nation and responsible development of Bosnian constitutionalism can be a sufficient framework for future generations who will live in peace and freedom with all their peculiarities as members of the internationally recognized Bosnian nation.